An AccountingModel for Watershed Ecological Compensation to Address Wa-ter Management Conflicts - Yang, Zhifeng; Han, Xi; Xu, Linyu; Yu, Bing (Journal of Environmental Accounting and Management, 2026)
Watershed ecological compensation is a powerful economic method used to address water management problems. In this study, we established an accounting model for watershed ecological compensa-tion based on STELLA software, using revenue functions to quanti-fy the profits of two cities during water use. The revenue functions included factors such as socio-economic water-use benefit, pollu-tion control cost and environmental externalities in the downstream area. This ecological compensation model can be used to address water-use disputes between upstream and downstream cities in the watershed area. Using the Guanting Reservoir Basin as a case study and considering the profit of each stakeholder, we calculated the payments under different scenarios of water quality and quantity within the provincial trans-boundary section. Our results indicated that (i) when the water quality of the inflow to Beijing (down- stream) is Grade V or IV as defined by the National Water Quality Standard of China, Zhangjiakou (upstream) should pay Beijing 92.04 or 48.19 million Yuan RMB, respectively; (ii) when the water quality of the inflow is Grade II, Beijing should pay Zhangjiakou 53.08 million Yuan RMB.